A Note on the Terms of Trade of Nigeria - Hawkins, E. K. (Review of Economic Studies, 1954)
A Note on the Terms of Trade of Nigeria E. K. Hawkins E. K. Hawkins Ibadan, Nigeria Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 22, Issue 1, 1954, Pages 47–56, https://doi.org/10.2307/2296223 Published: 01 January 1954